Negra sem reticências: corpo e corporeidade na poesia de escritoras afro-brasileiras - Paula, Claudemir da Silva [UNESP] (2015)
In a society that associates feminine beauty to physical (and cultural) white attributes and embodies ugliness in a black body it is easy to affirm that black women, who values their own body features, constitutes a vigorous process of negative concept and judgment resignification. This may happen due to a positive feeling towards their natural contours, which may presuppose a beauty able to make the need for compliance with the rules of hegemonic power fake, assuming, in that kind of confrontation, a skillful speech, enough to subvert representative forms of literature based on racist scenes of inferiority and objectification. This may destabilize the requirement of beautification as a condition for happiness in everyday experience. The body drawn from that perspective is beating Eurocentric binarism and reform. It is a black mode of being. The feminine idea assumed as a main form of activity, without essentialism, compares models devised in whitening parameters. For some black women, literature is the privileged field to forge the body deprived by interpretations of natural submission and combat places aspects (in) appropriated to those bodies that are contrary to the rules. As writers, placed in a privileged place of their own writing and, as announcers of the black condition, weave a 'de-colonial' poetics of the body. It is about the literary performance that we deal in this work. We intended to reflect on the corporality poetic of some Afro-Brazilian writers Alzira Rufino, Conceição Evaristo, Geni Guimarães and Miriam Alves, in convergence/divergence with the Eurocentric standard of beauty in the colonial paradigm of power. Specifically, it is the body - read as an element of black woman political emancipation, focusing solely on the rejection of subservience to the dictates of whiteness - the creation of their own standard of beauty and autonomy ideal conducted by disobedient choices and unsubmissive figurative types